2017
DOI: 10.1002/mds.27033
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the dorsal columns of the spinal cord for Parkinson's disease

Abstract: Spinal cord stimulation has been used for the treatment of chronic pain for decades. In 2009, our laboratory proposed, based on studies in rodents, that electrical stimulation of the dorsal columns of the spinal cord could become an effective treatment for motor symptoms associated with Parkinson's disease (PD). Since our initial report in rodents and a more recent study in primates, several clinical studies have now described beneficial effects of dorsal column stimulation in parkinsonian patients. In primate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 144 publications
1
51
0
1
Order By: Relevance
“…In keeping with what seen in our cases, other features can accompany the syndrome some years after the onset . SCS is a minimally invasive approach with an expanding number of off‐label indications: spasticity after stroke or spinal cord injury, peripheral vascular disease, neurogenic bladder, autonomic hyperreflexia, and gait disturbance in PD patients . Recently, a similar implant used in our patient was successfully used in the primate model of spinal cord injury .…”
Section: Casesupporting
confidence: 85%
See 1 more Smart Citation
“…In keeping with what seen in our cases, other features can accompany the syndrome some years after the onset . SCS is a minimally invasive approach with an expanding number of off‐label indications: spasticity after stroke or spinal cord injury, peripheral vascular disease, neurogenic bladder, autonomic hyperreflexia, and gait disturbance in PD patients . Recently, a similar implant used in our patient was successfully used in the primate model of spinal cord injury .…”
Section: Casesupporting
confidence: 85%
“…In recent years, studies in patients with pain or spinal cord lesions as well as in animal model of motor disorders have suggested that SCS might have positive effects on locomotion. Notwithstanding, the clinical experience in patients with Parkinson's disease (PD) has provided variable results, although a recent trial has found beneficial effects in a selected group or patients who also underwent deep brain stimulation (DBS) . Herein, we report for first time 2 cases of primary progressive freezing of gait who underwent SCS.…”
mentioning
confidence: 99%
“…Spinal cord stimulation (SCS) is an FDA-approved therapy for chronic pain. During the last decade, it has also emerged as a potential new therapy for treating freezing of gait, a notoriously difficult to treat manifestation of Parkinson's disease [19][20][21] .…”
mentioning
confidence: 99%
“…A repeat brain 18 FDG-PET, five months after SCS, revealed increased glucose metabolism in the bilateral frontal-parietal lobes as compared with that before SCS. SCS is a well-established therapy for treating chronic neuropathic pain [2]. We suggest SCS as an alternative approach for symptomatic treatment of FOG in patients with MSA-P.…”
Section: Case Reportmentioning
confidence: 97%